Determination of Optimum Nitrogen Level for Maximizing Yield of Two HYV Boro Rice Varieties in Bogura Region, Bangladesh (Bangladesh Agronomy Journal, 2024)
Application of N fertilizer is very crucial for rice, but both excessive and mild reduced productivity. A field experiment was conducted during the Boro 2021-2022 season to find out the optimum dose of N fertilizer for higher yield. The trial was conducted in a factorial RCBD design with three replications. Factor A: Two varieties of rice viz. BRRI dhan89 and BRRI dhan100 and B: Five Nitrogen levels i.e., 0, 90, 120, 150, and 180 Kg ha−1. Yield and yield-contributing traits varied significantly with N levels. BRRI dhan89 outyielded BRRI dhan100 due to its varietal potential and longer life cycle. The highest tiller number hill−1, panicle number hill−1, panicle length, filled grain panicle−1, grain yield, biological yield and harvest index and lowest spikelet sterility were obtained from 120 kg N ha−1 irrespective of variety. The result revealed that the combination of both varieties with 120 kg N ha−1 followed by 90 Kg N ha−1 in maximizing rice productivity while avoiding excess use of N fertilizer.Bangladesh Agron. J. 2024, 26(2): 41-48